Physical Activity as a Predictor of Cognitive Decline in an Elderly Essential Tremor Cohort: A Prospective, Longitudinal Study - Radler, Keith H.; Chapman, Silvia; Zdrodowska, Maria Anna; Dowd, Hollie N.; Liu, Xinhua; Huey, Edward D.; Cosentino, Stephanie; Louis, Elan D. (Frontiers in Neurology, 2021)
Background: Essential tremor (ET), one of the most common neurological diseases, is associated with cognitive impairment. Surprisingly, predictors of cognitive decline in ET remain largely unidentified, as longitudinal studies are rare. In the general population, however, lower physical activity has been linked to cognitive decline. Objectives: To determine whether baseline physical activity level is a predictor of cognitive decline in ET. Methods: 127 ET cases (78.1 ± 9.5 years, range = 55 - 95), enrolled in a prospective, longitudinal study of cognition. At baseline, each completed the Physical Activity Scale for the Elderly (PASE), a validated, self-rated assessment of physical activity. Cases underwent an extensive battery of motor-free neuropsychological testing at baseline, 1.5 years, and 3 years, which incorporated assessments of cognitive subdomains. Generalized estimating equations (GEEs) were used to assess the predictive utility of baseline physical activity for cognitive change. Results: Mean follow-up was 2.9 ± 0.4 years (range = 1.3 - 3.5). In cross-sectional analyses using baseline data, lower physical activity was associated with lower overall cognitive function as well as lower cognitive scores in numerous cognitive domains (memory, language, executive function, visuospatial function and attention, all p <0.05). In adjusted GEE models, lower baseline physical activity level significantly predicted overall cognitive decline over time (p = 0.047), and declines in the subdomains of memory (p = 0.001) and executive function (p = 0.03). Conclusions: We identified reduced physical activity as a predictor of greater cognitive decline in ET. The identification of risk factors often assists clinicians in determining which patients are at higher risk of cognitive decline over time. Interventional studies, to determine whether increasing physical activity could modify the risk of developing cognitive decline in ET, may be warranted.